Influence of customer perceived value on the online shopping intention of aquatic products under B2C E-commerce. (18th August 2018) - Lin, Wenhe; Xu, Anxin; Zheng, Qiuqin; Ke, Lubin; Lin, Jiahui
Abstract: Fresh food e-commerce enter into the golden period of development in the network age. Based on the perspective of consumers' perceived risk of aquatic products, 306 questionnaires were used to construct the impact model of perceived value and perceived risk on the intention of online shopping, and the moderating effect between the customer perception and online shopping intention was studied by using the website specialization as an moderator variable. The results show that consumers' perceived ease of use and usefulness will enhance their willingness to buy aquatic products, and perceived economic risks and perceived privacy risks have negative impact on online shopping aquatic products. The website specialization of aquatic product has a moderating effect among the consumer's perceived ease of use, usefulness and perceived economic risk, but it does not play a moderating role in the consumer's perceived privacy risk.